Public relations (PR) in corporate citizenship: beyond a mere reporting function? - Eiró-Gomes, Mafalda (2019)
Are PR professionals involved in the decision processes concerning Corporate Citizenship (CC) or are they only asked to report the organizations best practices? Are organizations committed to Corporate Social Responsibility (CSR) or Corporate Citizenship? In the framework of a pragmatist paradigm, a sequential explanatory mixed methods approach was developed. This method is a two phase design that is characterized by an initial quantitative phase of data collection and analysis, followed by a phase of qualitative data collection and analysis. An invitation to answer an online survey was sent to all 158 organizations that belonged to one portuguese association for the promotion of CSR (GRACE) in September 2018. Afterwards, face-to-face interviews with the CSR (CC) responsible were conducted to those organisations that answered the survey. The research showed that the social (philanthropic) area emerged as the most relevant one in all the organisations interviewed, even though the area seems to be under strong reformulations. Corporations seem however to dislike the concept of Corporate Citizenship.Communication professionals seem to have fewer responsibilities that those the researchers expected to find out at a strategic level.